Urban climate resilience in disinvested neighborhoods: the role of green infrastructure in addressing climate change threats - Goldsmith, Jenna (Kansas State University, 2024)
Climate change poses a unique threat in urban areas as they are typically home to diverse people from vastly different socio-economic backgrounds. Knowing that the consequences of climate change disproportionately impact communities of lower socio-economic status compared to others (Santamouris, 2023; Block et al., 2012), it is important to examine ways to boost the environmental resilience of these areas. Many of these communities have less access to necessary ecological resources and services, caused by a long history of disinvestment and discriminatory zoning laws that have increased segregation and decreased investment. One long-term impact of these trends is the higher vacancy levels within these neighborhoods. The culmination of these factors has made these neighborhoods vulnerable to the increasing threats and impacts of climate change. It is becoming increasingly crucial that cities focus on boosting the resilience of these historically disinvested neighborhoods to prevent future catastrophes. While high rates of urban vacancies can have vast negative impacts, these abandoned lots can provide a unique opportunity for cities to create positive change through revitalization projects in the face of the climate crisis. Climate resilience is understood as the ability of a community to cope and manage the impacts of climate change without a detrimental outcome (Pamukcu-Albers et al., 2021; Ramyar et al., 2021; Schleussner, Pfleidrer et al., 2021; Tauhid, 2018). This project has investigated how different types of green infrastructure can improve the environmental resilience of historically disinvested areas and how the site selection process for these greening projects could be reimagined to be more equitable and need-based. More specifically, this study explores how certain types of green infrastructure can mitigate the impacts of climate change-induced drought, flooding, and urban heat island effects. This study focuses on nine high-vacancy neighborhoods in Kansas City, Missouri, which have historically been impacted by redlining practices, to examine how site-specific implementations of green infrastructure can increase the community’s ability to withstand potential climate adversities. Environmental data was collected through public city resources related to the area's existing ecological conditions and hazards. This data was used for two rounds of GIS analytical mapping to gain knowledge of current conditions in the study area and locate suitable sites for potential revitalization efforts. A suitability model was created and used to produce suitability maps to discover potential sites. Furthermore, three different climate change models were analyzed to gain a baseline understanding of possible future climatic conditions and were used as a baseline for decision-making for green infrastructure typology design. With this information, a framework of green infrastructure typologies matched with suitable sites in the study area was created to improve the community’s resilience to drought, flooding, and urban heat island effects. The anticipated increase in resilience was exhibited through an overall theoretical network of green infrastructure that could be implemented in the study area. These findings offer more insights into the study and approach to improving urban climate resilience and contribute to the existing body of literature by identifying critical urban greening implementations for boosting climate resilience at various scales. The broader outcome of this study would be related to its potential implications in improving urban climate resilience in historically disinvested communities.
Keywords: Urban resilience; Climate change; Suitability mapping